Joget Bontek Dance of the Asli Tribe in Tanjung Padang Village, Meranti Regency, Riau Province - Syefriani, Syefriani; Idawati, Idawati; Putra, M Vitdriansyah; Megasari, Megasari (LPPM Institut Seni Indonesia Padangpanjang, 2024)
Meranti district community consists of a variety of ethnic groups, including Melayu, Tiong hoa, Minang, and others. One of the tribes that still exists in Meranti district is Asli Tribe. Asli Tribe has numerous arts that flourish and develop in their culture. The art that exists in Asli Tribe is Joget Bontek dance, Joget Bontek is a dance of joy and entertainment that is usually performed at wedding receptions, circumsicion ceremonies, welcoming guests, and others. Joget Bontek dance is comprised of dance movements, floor patterns, music, dynamics, themes, makeup and costumes that combined, make Joget Bontek dance become more interisting. To obtain accurate and precise data, the author uses analysis descriptive method using qualitative data. Data collection techniques in this research using non-participan observations, guided interviews, documentation using camera to take photographs and recordings of Joget Bontek dance in an effort to strengthen the research results obtained from secondary sources.